2017
DOI: 10.1177/0954406217736081
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and pressure drop of an upwardly two-phase flow through multi-hole orifices

Abstract: Experimental results on hydrodynamic behavior and pressure drop of two-phase mixture flowing upwardly in a pipe containing single- and/or multi-hole orifice plate are presented. It was found from the measurement of the void fraction upstream and downstream the orifices that the flow behavior is significantly affected by the layout of the orifice plate used and the flow starts to recover after approximately 7 D downstream the orifice. Furthermore, increasing orifice holes number results in decreasing the slip r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Figure 1 shows the experimental test rig. It is the same experimental test facility as that used previously by Zeghloul et al 31,32 The experiments were carried out by drawing tap water from the tank towards water flowmeters (rotameters) using a centrifugal pump from SAER ELETTROPOMPE. The latter was able to provide a total mass flow rate up to 40 m 3 /h.…”
Section: Experimental Setup and The Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the experimental test rig. It is the same experimental test facility as that used previously by Zeghloul et al 31,32 The experiments were carried out by drawing tap water from the tank towards water flowmeters (rotameters) using a centrifugal pump from SAER ELETTROPOMPE. The latter was able to provide a total mass flow rate up to 40 m 3 /h.…”
Section: Experimental Setup and The Methodologymentioning
confidence: 99%
“…Both air and water are mixed in the mixing unit and generate the air-water two-phase flow mixture. Details on the mixer unit are presented in the previous work of Zeghloul et al 32,33 Downstream the mixer, the air-water two-phase flow mixture flows through the Venturi in the vertical test section, then through a 90 bend, then a horizontal pipe section, and then a vertical 90 bend, then lastly to a vertical separating tank. The water flowed down through the bottom of the tank under the effect of gravity then recirculated again and the air is released into the atmosphere.…”
Section: Experimental Setup and The Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that the results of gas-liquid two-phase studies can help significantly improve scrubber performance and ease the facility upsizing process. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the results of gas-liquid two-phase studies can help significantly improve scrubber performance and ease the facility upsizing process. 14,15 Additionally, studying the pressure drop will contribute to a better understanding of the energy consumption of dust scrubbers. Because the self-excited dust scrubber is a differential pressure (throttling) device, the primary portion of the energy (pressure drop) is consumed during the throttling process at the choke.…”
Section: Introductionmentioning
confidence: 99%